2016
DOI: 10.4274/tjod.00334
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammation and oxidative stress in the etiology of primary ovarian insufficiency

Abstract: Objective:The aim of this study was to elucidate the etiology and treatment of primary ovarian insufficiency, which is of unknown cause in 95% of the cases.Materials and Methods:Thirty patients aged 18-40 years who presented to Dicle University Faculty of Medicine Clinic of Obstetrics and Gynecology between June 2012 and January 2014 and were diagnosed as having primary ovarian insufficiency based on their clinical and endocrinologic data, and 30 healthy controls were included in this study.Results:No signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…It is confirmed that oxidative stress index levels are elevated in primary ovarian insufficiency patients [ 16 ]. Moreover, previous literatures indicated that when ovary is exposed to some drugs related to oxidative stress, such as chemotherapeutic drugs, gamma irradiation, or polycyclic aromatic hydrocarbons, loss of primordial follicles is induced.…”
Section: Introductionmentioning
confidence: 91%
“…It is confirmed that oxidative stress index levels are elevated in primary ovarian insufficiency patients [ 16 ]. Moreover, previous literatures indicated that when ovary is exposed to some drugs related to oxidative stress, such as chemotherapeutic drugs, gamma irradiation, or polycyclic aromatic hydrocarbons, loss of primordial follicles is induced.…”
Section: Introductionmentioning
confidence: 91%
“…Preceding the last menstrual period, women undergo perimenopause, which lasts 4 years on average [140] and involves gradual, but highly fluctuating withdrawal of E2 [141]. The cessation of ovarian hormone function during perimenopause is associated with rises in chronic low-grade inflammation, which has been shown to promote ovarian insufficiency [142], and to increase the risk for developing obesity, AD, and autoimmune disorders [143]. For instance, the incidence of RA increases with menopause [143], and MS-related symptoms worsen after menopause [144].…”
Section: Menopausementioning
confidence: 99%
“…The endocrine transition of the perimenopause to the post-menopause, while associated with loss of reproductive function ( Brinton et al, 2015 ), is also associated with rise in chronic low-grade inflammation ( Yin et al, 2015 ). Chronic systemic inflammation accelerates ovarian failure ( Ağaçayak et al, 2016 ). Conversely, depleting proinflammatory cytokines IL-1α and IL-1β extends ovarian function and lifespan ( Uri-Belapolsky et al, 2014 ).…”
Section: Menopause Inflammation and Admentioning
confidence: 99%